THE ROLE OF AGENTS ON THE MARKETING OF BUFFALO IN NORTH TORAJA - Kasim, Kasmiyati; Lestari, Veronica Sri; Hastang, -; Rasyid, T. (Proceeding Buffalo International Conference, 2013)
The role of marketing agency in buffalo marketing has been recognised. The purpose of this research was  to study  the role of agent on buffalo marketing in North Toraja. The study was carried out in Bolu livestock market North Toraja form May to June 2012. Samples used for this study were all agents (10 people) in Bolu livestock market North Toraja. Data were analysed descriptively. The results of the study  indicated that 50% of the agents directly contacted  the seller  in the market. To get  the buyers, 60% of the agents also met  the buyers in the market in order  to  obtain  such information as  types of buffaloes they are looking for. Data also indicated that the time required by the buyers and the sellers to achieve an agreement of the price  through the help of an agent was normally one day. In conclusion, the role of the agents on buffalo marketing in North Toraja is important in terms of source of information for the sellers and buyers so that could accelerate the transaction process of  buffaloes.